Redescription of Acropsis Grant, 1958 (Orthoptera: Tettigoniidae: Phaneropterinae: Microcentrini) and description of new species from Brazilian and Colombian Amazon Rainforest - de Mello Mendes, Diego Matheus; Rafael, José Albertino (Zootaxa, 2020)
Acropsis Grant, 1958 is a monotypic genus with records only for Peru (type locality). Acropsis is being redescribed, including the Acropsis tectiformis species and two new species: Acropsis solimoesensis sp. nov. and Acropsis julianae sp. nov. The male internal genitalia and the stridulatory file morphology for the genus is being described for the first time. Furthermore, the genus is registered for the first time for Colombia (Caquetá) and Brazil (Acre and Amazonas) and additionally notes on the habitat are made.